Positive effect of salicylic acid application on productivity of papaya (Carica papaya) - Martin-Mex, Rodolfo; Nexticapan-Garcéz Ángel; Herrera-Tuz Rubí; Vergara-Yoisura, Silvia; Larqué-Saavedra Alfonso (Revista Mexicana de Ciencias Agrícolas, 2018)
For two years, was conducted an experiment with papaya (Carica papaya) cv. Maradol under field conditions in Yucatan in which was studied the effect of spraying low concentrations of salicylic acid (SA), in the productivity of fruit. The SA to concentrations of 0.01μM increased the percentage of hermaphroditic plants in 20% over the control and significantly increased the height and thickness of plants. This same concentration increased 19.7% the number of fruits per plant, in 2% of the fruit weight and 21.9% the yield per hectare. The SA at all concentrations tested, significantly increased the productivity variable analyzed.